Development of Inhalable Spray Dried Nitrofurantoin Formulations for the Treatment of Emphysema - Mathew N. Leslie; Nirmal Marasini; Zara Sheikh; Paul M. Young; Daniela Traini; Hui Xin Ong (MDPI AG, 2022)
A central characteristic of emphysematous progression is the continuous destruction of the lung extracellular matrix (ECM). Current treatments for emphysema have only addressed symptoms rather than preventing or reversing the loss of lung ECM. Nitrofurantoin (NF) is an antibiotic that has the potential to induce lung fibrosis as a side effect upon oral administration. Our study aims to repurpose NF as an inhalable therapeutic strategy to upregulate ECM expression, thereby reversing the disease progression within the emphysematous lung. Spray-dried (SD) formulations of NF were prepared in conjunction with a two-fluid nozzle (2FN) and three-fluid nozzle (3FN) using hydroxypropyl methylcellulose (HPMC) and NF at 1:1 w/w. The formulations were characterized for their physicochemical properties (particle size, morphology, solid-state characteristics, aerodynamic behaviour, and dissolution properties) and characterized in vitro with efficacy studies on human lung fibroblasts. The 2FN formulation displayed a mass mean aerodynamic diameter (MMAD) of 1.8 ± 0.05 µm and fine particle fraction (FPF) of 87.4 ± 2.8% with significantly greater deposition predicted in the lower lung region compared to the 3FN formulation (MMAD: 4.4 ± 0.4 µm; FPF: 40 ± 5.8%). Furthermore, drug dissolution studies showed that NF released from the 2FN formulation after 3 h was significantly higher (55.7%) as compared to the 3FN formulation (42.4%). Importantly, efficacy studies in human lung fibroblasts showed that the 2FN formulation induced significantly enhanced ECM protein expression levels of periostin and Type IV Collagen (203.2% and 84.2% increase, respectively) compared to untreated cells, while 3FN formulations induced only a 172.5% increase in periostin and a 38.1% increase in type IV collagen. In conclusion, our study highlights the influence of nozzle choice in inhalable spray-dried formulations and supports the feasibility of using SD NF prepared using 2FN as a potential inhalable therapeutic agent to upregulate ECM protein production.